DISFEMISME DAN FUNGSINYA DALAM KUMPULAN CERPEN SaiA KARYA DJENAR MAESA AYU - Icha Dwi Kartika; Ngusman Abdul Manaf (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The study is attracted by freedom of opinion is misused in communication activities by using words that have harsh meanings, giving rise to negative feelings. The research aims to find out the forms and functions of dysphemism in Djenar Maesa Ayu's short story collection SAiA. The research data in the form of words and phrases were obtained from the utterances of the characters in the story which contain elements of dysphemism. Data collection used the document technique, through the corpus linguistic method, namely the Indonesian Archipelago Corpus (KORTARA). Triangulation technique is used in validating research data. Research data analysis techniques include categorization, tabulation, and interpretation with substitution techniques to find agreement and differences in euphemism as a form of replacement. The findings show that there are eight forms of dysphemism and the most used form is the use of everyday technical terms, the other seven forms are the use of technical terms and jargon, figurative expressions (figuratively speaking), similes, circumlocutions, metaphors, clippings. (clipping), and hyperbole (hyperbola); Dysphemism in Djenar Maesa Ayu's collection of short stories SAiA functions as an expression to hide other people, to show dislike, to give a negative description of political actors, to express anger or annoyance, to reveal quarrels, and to amplify or exacerbate insults